Holoceńskie społeczności zbieracko – łowieckie zachodniej części Niżu Polskiego w kontekście analiz funkcjonalnych inwentarzy krzemiennyc - Pyżewicz, Katarzyna (Folia Praehistorica Posnaniensia, 2018)
This PhD project was aimed at presenting selected aspects of daily life of hunter-gathering societies in the western Polish lowlands. It was based on the microscopic analysis of flint artifacts supported by experimental data. The primary method comprised use-wear analysis of lithic surfaces. The interpretation of observed macro- and microtraces was based upon experimental data. The study reveals how flint artifacts were used, what was the relationship between physical actions and traces left on particular tools, and what kind of materials were utilized at the site. The reconstruction of flint hafting as well as identification of several techniques of blank production and tool retouching comprised an integral part of the study. The results of macroscopic and microscopic analysis, conducting experiments, typology and technology as well as raw material attributes made possible to reveal the relation between selection of the material, production technique, artifact forms, and their function. The rationale behind decisions at particular stages of production and utilization of flint artifacts has also been identified. The results of the project contribute to the recognition of behaviour of hunters and gatherers in the Holocene of Central Europe.